Seasonal and Temporal Variations of Field‐Aligned Currents and Ground Magnetic Deflections During Substorms. Issue 4 (19th April 2018) - Forsyth, C.; Shortt, M.; Coxon, J. C.; Rae, I. J.; Freeman, M. P.; Kalmoni, N. M. E.; Jackman, C. M.; Anderson, B. J.; Milan, S. E.; Burrell, A. G.
Abstract: Field‐aligned currents (FACs), also known as Birkeland currents, are the agents by which energy and momentum are transferred to the ionosphere from the magnetosphere and solar wind. This coupling is enhanced at substorm onset through the formation of the substorm current wedge. Using FAC data from the Active Magnetosphere and Planetary Electrodynamics Response Experiment and substorm expansion phase onsets identified using the Substorm Onsets and Phases from Indices of the Electrojet technique, we examine the Northern Hemisphere FACs in all local time sectors with respect to substorm onset and subdivided by season. Our results show that while there is a strong seasonal dependence on the underlying FACs, the increase in FACs following substorm onset only varies by 10% with season, with substorms increasing the hemispheric FACs by 420 kA on average. Over an hour prior to substorm onset, the dayside currents in the postnoon quadrant increase linearly, whereas the nightside currents show a linear increase starting 20–30 min before onset. After onset, the nightside Region 1, Region 2, and nonlocally closed currents and the SuperMAG AL (SML) index follow the Weimer (1994, https://doi.org/10.1029/93JA02721) model with the same time constants in each season. These results contrast earlier contradictory studies that indicate that substorms are either longer in the summer or decay faster in the summer. Our results imply that, on average, substorm FACs do not change with season but that their relative impact on the coupled magnetosphere‐ionosphere system does due to the changes in the underlying currents. Plain Language Summary: Earth is surrounded by electrical currents flowing in space. These currents, which can be 10, 000 times greater than domestic electrical supplies, can flow along the Earth's magnetic field and into the upper atmosphere and are linked to aurora. The size of this current depends on atmospheric conditions, with the upper atmosphere being a better conductor when it is sunlit, and the interaction between particles flowing from the Sun and the Earth's magnetic field. During space weather events known as substorms, which happen several times per day on average, the aurora brightens massively and the currents flowing into the upper atmosphere increase. Using data from the Iridium communications satellites, the increase in this current can be measured. While the strength of the day‐to‐day current varies with season, as expected from simple models of the system, the increases due to these space weather events are the same throughout the year. Key Points: While underlying field‐aligned currents (FACs) vary with season, currents from substorm activity show little seasonal variability FACs increase in the postnoon and premidnight quadrants before onset, with faster nightside increases occurring after dayside increases The time profile of substorm field‐aligned currents and SML agrees with a resistive‐capacitive model of the current system